Treatment Results of Major Salivary Gland Cancer by Surgery with or without Postoperative Radiation Therapy - Noh, Jae Myoung (Korean Society of Otorhinolaryngology-Head and Neck Surgery, 2010)
OBJECTIVES: This is to report treatment results of major salivary gland cancer by surgery with or without postoperative radiation therapy (PORT). METHODS: Between March 1995 and January 2006, 94 patients with primary major salivary cancer underwent curative surgical resection at Samsung Medical Center. The parotid gland was the most commonly involved (73, 77.7%), followed by the submandibular and the sublingual. Neck dissection was added in 28 patients, and PORT was individually recommended to those with risk factors. Seventy-five (79.8%) patients received PORT. PORT volume included primary tumor bed and pathologically involved regional lymphatics, and no additional effort was made for elective nodal irradiation. The median total doses were 56.0 Gy to primary site and 58.7 Gy to regional lymphatics. RESULTS: After median follow-up of 49 months, 21 patients had relapsed: 20 in PORT; and one in surgery alone group. As the first site of failure, distant metastasis was the most common (17 patients). Local recurrence occurred in three, and regional relapse in one. The lung was the most common site (10 patients), followed by the bone, and the brain. Five-yr disease free survival (DFS), local control, and overall survival (OS) rates were 74.4% and 94.7%, 96.0% and 100%, and 78.2% and 100% in PORT and surgery alone groups, respectively. On multivariate analysis, DFS was significantly affected by pN+ (hazard ratio [HR], 3.624; P=0.0319), while OS was by pN+ (HR, 7.138; P=0.0034) and perineural invasion (HR, 5.073; P=0.0187). CONCLUSION: Based on our experience, the patients with early stage major salivary gland cancer with low risk can be effectively treated by surgery alone, and those who with risk factors can achieve excellent local and regional control by adding PORT. Omitting elective neck irradiation in patients with N0 disease seems a feasible strategy under accurate clinical evaluation. An effort is needed to decrease distant metastasis through further clinical trials.